Factors aggravating or precipitating acne in Indian adults: A hospital-based study of 110 cases - Rani Maria George; Rajiv Sridharan (Wolters Kluwer Medknow Publications, 2018)
Background: Although acne is principally a disorder of adolescence, the number of adult patients with acne is increasing. Adult acne is defined as the presence of acne beyond the age of 25 years. There is relatively few data on the prevalence and studies of acne in adult population. Aim and Objectives: To analyze the various factors that aggravate or precipitate acne vulgaris in Indian adults. Materials and methods: The study was done at the Department of Dermatology at a tertiary care center in Kerala for a period of 1 year. A total of 110 patients above the age of 25 year diagnosed clinically as acne vulgaris were included in the study. A detailed history regarding age of onset, duration, type of acne, family history, whether there was any exacerbation related to food, cosmetics, drugs, emotional stress, seasonal variation, sunlight, sweating, pregnancy, menstruation and smoking was taken. Results: Majority of patients with adult acne were in the age group 26-30 years and there was a clear female preponderance. Persistent acne was more common than late onset acne. Food items and cosmetics were attributed to exacerbation by 47.3% and 40% of patients respectively; 32.7% patients had exacerbations during stress, 26.4% following sun exposure and 23.6% after sweating. About 48% patients had first degree relatives with present or past history of acne. Most of the female patients had premenstrual flare of acne, which was much more common among patients with persistent acne. Pregnancy had no effect on acne in majority of patients. Seasonal variation was observed in 44.5% patients, most of them showing exacerbation in summer months. Conclusion: Acne as a disease lasts longer, persists into adulthood and requires treatment well into the forties. Unlike teenage acne, where males tend to be affected more commonly, post adolescent acne mainly affects females. It is therapeutically rewarding to identify the concerned triggers and aggravating factors and be able to deal with them.